INVESTIGATION OF THE PARTICIPATION OF SILICONE IN THE PROCESS OF SOPOLYMERIZATION - I.O. Hojiyev; S.I. Nazarov; H.Q.Razzakov; F.I. Ostonov; G'.Q. Shirinov (Journal Park Publishing, 2023)
This article is based on the sol -gel method hybrid organic-inorganic composites synthesis and electronic appearance of colloidal silica, properties of composites based on nitrogen-retaining polycompounds given.
Keywords: sol -gel, vinylmorpholine, copolymer, component, monomer, colloidal silica.